Species profiles life histories and environmental requirements of coastal fishes and invertebrates (South Florida)--King and spanish mackerel - Godcharles, Mark F.; Murphy, Michael D. (Washington, D.C. U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.58)
Keywords: Invertebrates; Fishes; History; King and spanish mackerel--South Florida